Youth Organizations as Reserve Components in Support of National Defense - Susilawati, Susilawati; Udayana, Agung; Navalino, Djoko Andreas; Supriyadi, A. A. Supriyadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
A strong nation refers to a nation that has large national resources, whether human, natural or artificial resources. Indonesia's human resources are the country's most important defense assets in protecting sovereignty, territorial integrity and the safety of the Indonesian nation and state. In this case, youth organizations can actually grow as a reserve component to overcome military and non-military threats, both in times of war and peace. Considering that the reserve component will play an important role in supporting national defense, the government must make every effort to build this component based on the national defense posture which includes military and non-military defense. Therefore, it is necessary to create a legal umbrella so that reserve components originating from youth organizations can be mobilized and demobilized as needed.